2018
DOI: 10.1002/2211-5463.12412
|View full text |Cite
|
Sign up to set email alerts
|

Loss of scinderin decreased expression of epidermal growth factor receptor and promoted apoptosis of castration‐resistant prostate cancer cells

Abstract: Most patients with prostate cancer will eventually develop the castration‐resistant form characterised by metastasis. Cytoskeleton constituents, including F‐actin, play important roles in maintaining epithelial integrity and their disruption is a major cause of cancer progression. We previously showed that scinderin (SCIN), an important regulator of F‐actin organisation, is highly expressed in poorly differentiated cancer tissues. This study aimed to explore the mechanism of its regulation of cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Although the correlation between SCIN and cancer has been revealed, gradually, the role of SCIN in tumor development and progression was controversial among different researches. SCIN expression in megakaryoblastic leukemia cells promoted cell apoptosis and impaired cell proliferation and tumor formation (Zunino et al, 2001), which is contrary to our study and others (Lai et al, 2018; Qiao et al, 2018). Another study found high levels of SCIN expression in gastric cancer tissue correlated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the correlation between SCIN and cancer has been revealed, gradually, the role of SCIN in tumor development and progression was controversial among different researches. SCIN expression in megakaryoblastic leukemia cells promoted cell apoptosis and impaired cell proliferation and tumor formation (Zunino et al, 2001), which is contrary to our study and others (Lai et al, 2018; Qiao et al, 2018). Another study found high levels of SCIN expression in gastric cancer tissue correlated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 99%
“…In prostate cancer, SCIN knockdown significantly downregulated the protein expression of epidermal growth factor receptor (EGFR), impaired cell proliferation-mediated by epidermal growth factor, and inhibited the signaling pathway activation of the downstream mitogen-activated protein kinase (MEK) and extracellular signal-regulated kinase (ERK). SCIN knockdown promoted prostate cell apoptosis by inhibition of B-cell lymphoma-extra-large (Bcl-xl) expression and caspase signaling (Lai et al, 2018). However, the clinical significance and molecular mechanism for SCIN in CRC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The EGFR maintains cell survival by the following main cascades: The SRC proto-oncogene, non-receptor tyrosine kinase (Src)/mitogen-activated protein kinase (MAPK) cascade, and phosphatidylinositol 3-kinase (PI3K)/AKT signaling. Src phosphorylates MAPK kinase (MEK) with/without the paxillin (PXN) intermediate, followed by MAPK1 (also named extracellular signal-regulated kinase (ERK)) activation to upregulate pro-survival factors, such as BCL2-like 1 (Bcl-xL), matrix metalloproteases (MMPs), and Elk1/c-Fos [ 36 , 37 , 38 , 39 , 40 ]. Meanwhile, MEK phosphorylates Y-box-binding protein 1 (YB-1), which collaborates with ribosomal S6 kinase (RSK) and Raf-1 for the survival of gene expressions [ 41 , 42 ] ( Figure 2 ).…”
Section: Egfr Signalingmentioning
confidence: 99%
“…Src could activate both AR signaling and MEK/ERK or MEK/Y-box binding protein 1 (YB-1) signaling, which activate growth-related transcription factors. This figure is a summary of reference [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. A black solid arrow represents signal transduction; a red arrow represents cell fate.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation